A patient-specific timing protocol for improved CT pulmonary angiography - Yixiao Zhao; Logan Hubbard; Shant Malkasian; Pablo Abbona, M.D.; Vijay Bosemani, M.D.; Sabee Molloi, Ph.D. (Research in Diagnostic and Interventional Imaging, 2023)
Rationale and objectives: To improve the image quality of CT pulmonary angiography (CTPA) using a patient-specific timing protocol. Material and methods: A total of 24 swine (48.5 ± 14.3 kg) underwent continuous contrast-enhanced dynamic CT acquisition over 30 s to capture the pulmonary arterial input function (AIF). Multiple contrast injections were made under different cardiac outputs (1.4–5.1 L/min), resulting in a total of 154 AIF curves. The volume scans with maximal enhancement in these AIF curves were retrospectively selected as the reference standard (group A). Two prospective CTPA protocols with bolus-tracking were then simulated using these AIF curves: one used a fixed delay of 5 s between triggering and CTPA acquisition (group B), while the other used a specific delay based on one-half of the contrast injection duration (group C). The mean attenuation, signal-to-noise (SNR) and contrast-to-noise ratios (CNR) between the three groups were then compared using independent sample t-test. Subjective image quality scores were also compared using Wilcoxon-Mann-Whitney test. Results: The mean attenuation of pulmonary arteries for group A, B and C (expressed in [HU]) were 870.1 ± 242.5 HU, 761.1 ± 246.7 HU and 825.2 ± 236.8 HU, respectively. The differences in the mean SNR and CNR between Group A and Group C were not significant (SNR: 65.2 vs. 62.4, CNR: 59.6 vs. 56.4, both p > 0.05), while Group B was significantly lower than Group A (p < 0.05). Conclusion: The image quality of CT pulmonary angiography is significantly improved with a timing protocol determined using contrast injection delivery time, as compared with a standard timing protocol with a fixed delay between bolus triggering and image acquisition.